2004
DOI: 10.1042/bj20040099
|View full text |Cite
|
Sign up to set email alerts
|

The chitinase 3-like protein human cartilage glycoprotein 39 inhibits cellular responses to the inflammatory cytokines interleukin-1 and tumour necrosis factor-alpha

Abstract: Expression of the chitinase 3-like protein HC-gp39 (human cartilage glycoprotein 39) is associated with conditions of increased matrix turnover and tissue remodelling. High levels of this protein have been found in sera and synovial fluids of patients with inflammatory and degenerative arthritis. In order to assess the role of HC-gp39 in matrix degradation induced by inflammatory cytokines, we have examined its effect on the responses of connective tissue cells to TNF-alpha (tumour necrosis factor-alpha) and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(175 citation statements)
references
References 49 publications
5
165
0
2
Order By: Relevance
“…Recent studies have shown that purified YKL-40 promotes connective tissue growth, provides a signal through kinase-mediated signaling pathways (47), and inhibits fibroblast responses to IL-1 through its effects on these pathways, resulting in a reduction in MMP-1, MMP-3, and IL-8 production (48). These data support the concept of a protective repair response elicited by chondrocyte-derived YKL-40.…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies have shown that purified YKL-40 promotes connective tissue growth, provides a signal through kinase-mediated signaling pathways (47), and inhibits fibroblast responses to IL-1 through its effects on these pathways, resulting in a reduction in MMP-1, MMP-3, and IL-8 production (48). These data support the concept of a protective repair response elicited by chondrocyte-derived YKL-40.…”
Section: Discussionmentioning
confidence: 53%
“…Tumor necrosis factor-a in a process that could be mediated through NF-kB is mainly responsible for HDAC recruitment to this promoter (Bhat et al, 2008). Of note, YKL-40 has been shown to induce migration of endothelial cells as well as proliferation and protection against inflammatory damage in a variety of cells (Ling and Recklies, 2004).…”
Section: Hdacs and Regulation Of Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…Clinical research has shown that high levels of YKL-40 are found in the serum of patients suffering from chronic asthma and also in patients with severe arthritis [21][22][23]. Immune response studies have linked YKL-40 to a down-regulation of the inflammatory mediators MMP (matrix metalloprotease) 1 and MMP3 and IL-8 (interleukin-8), suggesting a protective influence under innate immune response conditions [24]. YKL-40 has been shown to have the ability to act as a growth factor for skin and fetal lung fibroblasts [25].…”
Section: Introductionmentioning
confidence: 99%